Nation, constitutionalism and Buddhism in Sri Lanka - De Silva Wijeyeratne, Roshan (Routledge contemporary South Asia series, 2014)
"Focusing on Sri Lanka, this book offers a new perspective on contemporary debates about nationalism in South Asia. It looks at the 'capture' of Buddhism by militant Sinhalese nationalism in the colonial and postcolonial periods, and the framing of subsequent key constitutional legal moments. The book combines the dynamics of constitutionalism with the orbit of historical, political and anthropological scholarship on the cosmology of Sinhalese Buddhism and its relation to Sinhalese Buddhist nationalism. It explores four cases of legal-constitutional moments and offers a unique contribution to the politics and history of devolution in Sri Lanka. The book goes on to examine the way in which Buddhism, and particularly the Asokan state model, may in fact provide the intellectual resources for decentralized government beyond Sri Lanka in other parts of the Theravda Buddhist world, such as Thailand and Burma. Presenting a timely analysis given the intensification of Sri Lanka's civil war since the election in 2005 of President Mahinda Rajapakse on an overtly ultra nationalist Sinhalese Buddhist platform, this book is of interest to scholars of South Asian Studies, anthropology, sociology, ethnicity and political science"--